Relationship of self-esteem and happiness from the positive psychology among intercultural nursing students - Marco Alberto Núñez Ramírez; Gloria Esthela González Quirarte; Rosario del Carmén Realpozo Reyes (Enfermería Actual de Costa Rica, 2015)
Introduction: There are contradictions on the relationship between self-esteem and happiness: it exists for some researches, for others it does not, and even some argue that self-esteem affects happiness. These variables are elementary for the practice of Nursing; however, their study is small within intercultural environments. The objective of this research is to know the association between self-esteem and happiness among Intercultural Nursing students from the positive psychology. Method: A quantitative, descriptive, transversal and correlational, research with a non-experimental design was realized, with a sample of 55 students of Intercultural Nursing. Two questionnaires were applied: the scale of Rosenberg self-esteem and happiness of Lima scale. Results: High levels of self-esteem and happiness were obtained. Through correlation of Pearson and hierarchical regression we found that self-esteem is associated in negative and positive way with certain factors of happiness; the same thing happened in the level of influence. Conclusion: In positive psychology is possible to associate variables such as self-esteem and happiness as strengths. Much more in the case of Intercultural Nursing students which have the aim to contribute to the indigenous communities development, that require nurses with favorable levels of self-esteem and the perception of subjective well-being to counteract an historical legacy of backwardness. From positive psychology is possible that this educational model will contribute to the mutual enrichment and empowerment within the work of the Intercultural Nursing.